Assessment of high temperature effects on grain yield and composition in bread wheat commercial varieties - Tomás, Diana (2020)
Wheat is one of the most important cereals for food and feed, and it is, therefore, necessary to determine the e ects of short-term high temperature events (heatwaves) during grain filling. These heatwave events are increasingly common, especially in Portugal. In this work, seven commercial varieties recommended for production in Portugal were submitted to one-week high temperature (HT) treatment ten days after anthesis to evaluate heat e ects on grain yield and quality. Grain yield parameters, such as grain number and weight, were evaluated as well as grain composition through attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy. Variation in HT response between varieties was detected. Grain number and weight tended to decrease in most varieties analyzed. However, two varieties proved to be more resilient since grain number and weight remain unaltered in the Bancal variety, which is the one with better yield results, and even increased in the Pata Negra variety. Regarding grain composition, the comparison between ATR-FTIR spectra of milled grains from control and HT plants revealed alterations in peaks assigned to polysaccharides and proteins. Additionally, a model was built based on nitrogen elemental analysis to predict protein content in flour samples through spectral data that corroborated the di erences identified by spectra profile comparison. Moreover, both analyses showed that the intervarietal diversity observed in control conditions was significantly reduced in HT treated plants. The results obtained highlight the intervarietal diversity of wheat response to HT, regarding grain yield parameters, grain composition, and particularly, protein content